Distribuição e partição geoquímica de fósforo em sedimentos estuarinos do Rio Jaguaribe/Ce - Paula Filho, Francisco José de (2004)
The goal of this work is to establish the geochemistry distribuition of the total phosphorus as well as its geochemistry fraction that exist in the sediments of the Jaguaribe River estuary, in the state of Ceara. Information from this project show that the estuary system presents a total phosphorus concentration, inorganic and organic in the sediments, inferior of the others natural systems that presents phosphorus limitation. The results produced in two campaigns in the estuary water-course were submited to a statistical analysis ond they don´t show significant alteration in the total phosphorus stock settled in sediments in periods of time in differents gotherings. Nevertheless, three of gatherings presented statistical differentiation regarding to the others and it can be a water retention or to the urban affluents stablishments or agriculture in the estuary region located between Aracati and love channel. Both hypothesis need specific samples and they were not considered in this project. The profiler of evidence show a slight tendence in increasing of concentration of three phosphorus fractions observed (Total phosphorus, total inorganic and, total organic) in superior layers. It indicates that in recent years the estuary has been like a retainer of phosphorus, and this can rebound in the productivity of the ecological system. Out of statistical correlation of the inorganic fractions with the geochemical boaders (total organical matter and easely oxidizable, iron and carbonates) and with the hydrochemical model (salinity, pH, dissolved oxigen) we conclude the predominance of ferric and carbonates from of phosphorus in superficial sediments located in Aracati and the mouth of the river of the estuary. Seemingly the ambient conditions of the main estuary water-course contribute for a phosphorus kidnap from the water and your deposition in sediments. In a different way of what happen in secondary water-course (Gamboa) where the anoxidal conditions contribute for its maintenance in water and/or the liberation of the sedimental river-bed. The impact of a great number of dams along of Jaguaribe River is observed in the results from the phosphorus found into the waters. Becouse the information corroborate the retention of nutrients in the continental part of the estuary. On the other hand, this fraction is revolved in the mouth of the river because the erosion in the coast that happen in the mouth of the river, because of a low fluvial drained and the retention of sediments for many dams in the river. The use of the Spectrofotometria and Nuclear Magnetic Ressonance in the organical fraction especialization stablish a very important instrument in the ambiental observance of the region, because it permits to qualify and to quantify the kinds of organic phosphorus found in the sediments, nevertheless the use methodology of extraction still needs get better.